Komparasi Daya Saing Kopi Indonesia dan Vietnam di Pasar ASEAN China Free Trade Area (ACFTA): Analisis Keunggulan dan Faktor-faktor yang Memengaruhinya - Br Tarigan, Anggreni Karolin; Noor, Trisna Insan; Renaldy, Eddy; Wiyono, Sulistyodewi Nur (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Southeast Asia is one of the most active regions in establishing regional trade cooperation, one of which is through the formation of the ASEAN China Free Trade Area (ACFTA), which came into effect in 2010. Indonesia and Vietnam play an important role in the export of agricultural products, particularly coffee, which is one of the strategic products of the plantation sub-sector. Coffee is a flagship commodity that plays a significant role in international trade, including within the ACFTA region. This study aims to compare the export competitiveness of Indonesian and Vietnamese coffee, specifically for products with HS code 0901.11 (unroasted, uncaffeinated coffee), and to analyze the factors influencing this competitiveness during the period 2001–2023. A quantitative approach was used through Revealed Comparative Advantage (RCA) analysis and panel data regression. The results indicate that Vietnam has a higher comparative advantage than Indonesia in the ACFTA market, with an average RCA index value of 38.78. Additionally, the variables of exchange rate, inflation, and trade openness index were found to significantly influence the competitiveness of Indonesia and Vietnam's coffee exports in the ACFTA region. Meanwhile, the implementation of the ACFTA agreement did not show a significant impact on the competitiveness of coffee exports from both countries.